The Influence of Teachersâ Performance Empowerment in Improving the Quality of Education in the Elementary Schools - Subroto, Waspodo Tjipto (EDUCARE, 2012)
ABSTRACT: Teachers have importance position and roles to increase the quality of teaching and learning process, so that the performance of the teachers must also be improved. Empowering the teachersâ performance is visible to increase the quality of education in the elementary schools in Surabaya city, East Java, Indonesia. This study is intended to explore on how to implement the empowerment for teachers (education qualification, training, and briefings) related to education quality. The study was conducted to the sample of 174 small clusters by using stratified cluster sampling technique. Applying structural equation modeling analysis, the research-intensive as the findings followed. This research finding showed that education qualification of teachers influenced the teachersâ performance and also the education quality at elementary schools. Besides that, it influenced education in service training to teachersâ performance and education quality. Moreover, teachersâ professional training also influenced the performance and the education quality. The research conclusion stated that empowerment of teachers has influenced the increase of performance with indicators of knowledge, attitude, and skills to increase the education quality. So, the quality of elementary schools with value indicator increased not only the quantity but also quality of teaching and learning process.KEY WORDS: Teacher performance, empowering, Indonesia human resources, elementary schools, teaching and learning process, and quality of education.About the Author: Dr. Waspodo Tjipto Subroto is Senior Lecturer at the Faculty of Education UNESA (Universitas Negeri Surabaya or State University of Surabaya), Jalan Kentingan, Surabaya City, East Java, Indonesia. Mobile: +6281333213333. E-mail: waspodotjipto@yahoo.co.idHow to cite this article? Subroto, Waspodo Tjipto. (2012). âThe Influence of Teachersâ Performance Empowerment in Improving the Quality of Education in the Elementary Schoolsâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.65-78. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 11, 2012); Revised (July 13, 2012); and Published (August 17, 2012). Â Â Â Â Â